ANALISIS KINERJA SISTEM INFORMASI AKUNTANSI (SIA) PERBANKAN DI SURAKARTA - Hernawati Pramesti; Dyah Ayu Puri Palupi; Mary Budiarti (Fakultas Bisnis UKDW, 2009)
Purpose of this research is to hnow inforrnation qualityfactor influence, involvement of consumer, management support from, impact to organizational consumer and size to performance sIA banking in Surakarta. Resemeher applies primary data with population of all manager at banking in Surakarta. Audition of samplewithpurposive sampling. Data analytical technique applied is validity test and reliability test, classic assumption test, doubled regression analysis, test t, F test, and coeficient ofdetermination. Result ofresearch indicates that quality of information, irwolvement of consurner, ntanagement support from, impact to consunter in/luential positive to accounting information system performance at banking in Surakarta. While organizational size had an effect on negativity to accounting information system pedormance at banhing in Surakarta.Keyword: Accounting information system, involvement and banking